Pengaruh Masa Transisi Remaja Menuju Pendewasaan Terhadap Kesehatan Mental Serta Bagaimana Mengatasinya - Safitri, Melyana (Jurnal Pendidikan Ilmu Sosial, 2021)
Adolescence is a time when there are many processes experienced by an individual, both physically and psychologically. For this reason, this scientific research aims to be able to describe what developments occur during adolescence towards maturity and its effects on mental health from the anxiety they experience. The method used in this research is a literature study from various data reference sources, also give them some questionnaires. From this analysis, I will look at what problems they generally experience and what is the background of these problems in general. How do they motivate themselves, is it enough with the role of self-motivation, then, do they need motivation from other people in dealing with this problem, then how is the context devoured by someone who is more closed off, and those who think the problems and stress they experience are just winds. Then, how about their mental health today? With this condition, the role of self-motivation, such as self-love and self-awareness, plays an important role. The role of the closest people is also important in helping them express their feelings.